Znaczenie terminali LNG na wspólnym rynku energii UE - Ruszel, Mariusz (Polityka i Społeczeństwo, 2021)
The new geopolitical challenges increase the need to do more to strengthen energy security in Europe. For this reason, the EU implements the principles of competition and liberalisation of the natural gas market in order to create an internal energy market as well as build and modernise the gas infrastructure. The question arises, what role will LNG terminals have in the EU internal energy market. The overall aim of this article, based on politological analysis, is to answer following questions: to what extent LNG terminals contribute to the integration and the fragmentation of the internal energy market? Is the location of LNG terminals affects the development of the centres of natural gas distribution in different parts of Europe? What factors can strengthen the potential of LNG terminals in Europe?